Empirical study on Cambodian children's drawing by the S-HTP method (Year 2) - SUZUKI Mitsuo (美術教育, 2022)
The Japan Team of Young Human Power (JHP) , a nonprofit corporation,and Small Art School have been actively supporting Cambodia. They have been facilitating teacher training and curriculum development in art education. As a result, an art subject will be newly introduced in the new Cambodian education curriculum. The new Cambodian curriculum will include one hour of art class per week and will be implemented in elementary schools. Prior to art education beginning in Cambodia, we investigated if there was a difference in the students' development of creative expression in drawing depending on whether the students had experience with the picture development method called the S-HTP (Synthetic House-Tree-Person technique) . We found that children with learning experiences had more expressive power. They used their imagination based on their real life experiences while expressing their creativity through drawing.